Seismic imaging of fluid-filled inherited structures of the Northern Thessaly (Greece) seismic gap - Napolitano, F.; Amoroso, O.; De Novellis, V.; Adinolfi, G. M.; De Matteis, R.; Sansosti, E.; Russo, D.; Caputo, R.; Convertito, V. (Frontiers in Earth Science, 2023)
We present the first seismic imaging of the crustal volume affected by the March-April 2021 Thessaly sequence by applying a 3D seismic tomography to the aftershocks recorded by an unprecedented number of stations. The results, in terms of VP, VS, and VP/VS ratio and earthquakes’ location parameters, depict blind fluid-filled inherited structures within the Northern Thessaly seismic gap. The tomographic images highlight the basal detachment accommodating the Pelagonian nappe onto the carbonate of the Gavrovo unit. The high VP/VS (>1.85) where most of the seismicity occurs increases from SE to NW, showing possible fluid accumulation in the NW edge of the seismogenic volume that could have contributed to the sequence evolution. The aftershock relocations correlate well with the fault planes of the three mainshocks proposed by several geodetic models, but also show additional possible faults sub-parallel and antithetical to the main structures, not to be overlooked for future seismic risk mitigation.